Vpliv matematične interesne dejavnosti na matematične dosežke mlajših učencev - Lipovec, Alenka (Revija za elementarno izobraževanje, 2014)
Influence of Math Club Activities on Primary Students’ Mathematics Achievement. An intervention program called Didactic pentagon is described. Participants are teachers, students, parents, pre-service teachers and teacher educators. The programme is shaped as a math club activity. Empirical results focus on comparing mathematics achievements of students included in the programme and mathematically promising students taking part in TIMSS 2003. Experimental group has surpassed control group in overall results. Statistically significant differences in favour of experimental group can be found at intermediate international benchmark of mathematics achievements and at problem solving cognitive domain. The results can be assigned to pentagon activities guided by pre-service teachers. Cooperation between university and schools has evidently overcome the lack of pre-service teachers’ experience and helped in raising mathematical knowledge of school youth.